2019
DOI: 10.1080/07908318.2019.1619751
|View full text |Cite
|
Sign up to set email alerts
|

When ‘home languages’ become ‘holiday languages’: teachers’ discourses about responsibility for maintaining languages beyond English

Abstract: When 'home languages' become 'holiday languages': teachers' discourses about responsibility for maintaining languages beyond English. Language, Culture and Curriculum, 33 (3). pp. 213-227.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…The findings suggest that when lecturers (in this case teaching Chinese as a foreign language) did use translanguaging, they noted great improvement in their students' acquisition of the English language ("predominantly employed for explanatory and elicitation functions", ibid., p. 359) and course-specific knowledge. This suggests a close link between language use and knowledge-building (Cunningham 2019;Meyerhöffer and Dreesmann 2019).…”
Section: Science Education: Oscillation Between Everyday and Scientif...mentioning
confidence: 89%
“…The findings suggest that when lecturers (in this case teaching Chinese as a foreign language) did use translanguaging, they noted great improvement in their students' acquisition of the English language ("predominantly employed for explanatory and elicitation functions", ibid., p. 359) and course-specific knowledge. This suggests a close link between language use and knowledge-building (Cunningham 2019;Meyerhöffer and Dreesmann 2019).…”
Section: Science Education: Oscillation Between Everyday and Scientif...mentioning
confidence: 89%
“…This perspective is especially persistent among monolingual teachers, while, as Premier and Miller (2010) found, educators who had experienced learning a second language were more sensitive to the language barrier. In recent years, such a deficit perspective has been challenged by many scholars who take a strengths-based approach to CALD learners and acknowledge the importance of students' linguistic and cultural repertoires for learning (Cunningham, 2020).…”
Section: Language Barriermentioning
confidence: 99%
“…Also in the UK, studies have found that teachers and parents hold similar opinions, either explicitly or implicitly (Cunningham, 2019a(Cunningham, , 2019bCurdt-Christiansen & LaMorgia, 2018;Weekly, 2018). Curdt-Christiansen & LaMorgia (2018) explored FLP in Chinese, Italian and Pakistani communities in the UK.…”
Section: Educational Policy Eal Children and Teachers' Attitudesmentioning
confidence: 99%
“…When tracing the roots of family language policies, researchers have pointed out that teachers' attitudes towards migrant children's home language and cultural background as well as their discourse about home language practices may play an instrumental role in developing children's and their parents' views on their own language and cultural heritage, either positively or negatively (Conteh & Brock, 2011;Cunningham, 2019aCunningham, , 2019bSong, 2019;Weekly, 2018). Cunningham (2019a;2019b), for example, examined the discourse of a group of UK teachers with regard to their attitudes towards EAL children's home language maintenance and literacy practices. While the teachers seemed to support the notion of additive bilingualism, their support tended to be rhetorical.…”
Section: Educational Policy Eal Children and Teachers' Attitudesmentioning
confidence: 99%